Technology at the service of surgery in a new technique of autotransplantation by guided surgery: a case report - Mena Álvarez, Jesús; Riad Deglow, Elena; Quispe López, Norberto; Rico Romano, Cristina; Zubizarreta Macho, Álvaro (My University, 2020)
Background: The aim of this case report was to use a surgical technique for autotransplantation of tooth using virtually planned 3D printed surgical templates for guided osteotomy preparation of the recipient of donor tooth. Case presentation: An 18-year-old male patient received autotransplantation of the right mandibular third molar to replace an included right second molar. This procedure was based on guided implant surgery methods by superimposition of DICOM files and 3D data sets of the jaws. In order to design a 3D-printed template with the aid of a fully digital workflow; the third molar was conserved in PRGF during the surgical procedure and the tooth socket was prepared with a template and the help of a 3D-printed donor tooth copy in order to prevent iatrogenic damage to the donor tooth. This template and replica were manufactured using 3D-printing techniques. The transplanted tooth was placed in infra-occlusion and fixed with a suture splint and root canal therapy was performed 15 days later. The intervention was be accomplished by performing preplanned virtual transplantations with guided osteotomies to ensure accurate donor tooth placement in the new recipient site. The 24 months follow-up showed physiological clinical and radiologic results compatible with healing periradicular tissues. Conclusions: This approach enables the planning and production of a 3D printed surgical template using the latest diagnostic methods and techniques of guided implant surgery. These accurate virtually predesigned surgical templates and printed analogues of the donor tooth could facilitate autotransplantation, ensuring an atraumatic surgical protocol